Effectiveness of cataract surgery with intraocular lens implantation: a comparative study between extracapsular cataract extraction and phacoemulsification - Rizal AM,; Muhammad M,; Aljunid SM,; Normalina M,; Faridah HA,; Chuah KL,; Suzainah Y,; Zainal M,; Azman AB, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2011)
Introduction : A randomised single blinded clinical trial comparing the effectiveness of two methods of cataract surgery with intraocular lens implantation: extracapsular cataract extraction (ECCE) and phacoemulsification (PEA) was carried out at Universiti Kebangsaan Malaysia Medical Centre (UKMMC) between March 2000 and August 2001. Methodology : The effectiveness of cataract surgery was assessed from the quality of life specifically for vision via Visual Function 14 (VF-14) preoperatively, one week, two months and six months after surgery. Result : The result showed that there was a significant increased in VF-14 scores after a week, two months and six months post-operation compared to the score before surgery for both techniques. However there was no significant difference in VF-14 scores when compared between ECCE and PEA. Conclusion : This study indicated that both techniques give equal benefit to cataract patients. Since effectiveness of cataract surgery with intraocular lens implantation is unrelated to operative procedures, less costly technique should be promoted.